Effect of jet-to-plate spacing in laminar array jets impinging - Aldabbagh, L. B. Y.; Mohamad, A. A. (Springer, 2007)
The rate of heat transfer from a plate due to impinging of an array of jets was investigated. The effect of jet-to-plate spacing in a confined array of impinging laminar square jets was investigated numerically through the solution of Navier Stokes and energy equations. The simulation is carried out for the jet-to-plate spacing between 2 B and 20 B and for jet-to-jet spacing of 4 B, where B is the jet width. Five in-line jets subjected to across-flow were used in this investigation. Also, six different ratios of jet to cross-flow velocity are simulated (0.5, 1.0, 2.5, 5, 7.5 and 10) for the jet Reynolds number of 200. The predicted results show a formation of one or two ground horseshoe vortices between the jets. In addition, a horseshoe vortex forms at different position between the orifice and impinging plates due to the interaction of two jets before they combine. The number of the ground horseshoe vortex and its size are strongly affected by the jet-to-plate spacing and by jet to cross-flow velocity ratio. The effect of jet-to-plate spacing and jet to cross-flow velocity ratio on heat transfer is presented and discussed.
Keywords: jet-to-plate spacing; cross-flow; impinging jets